Analisis Tingkat Profitabilitas dan Likuiditas terhadap Struktur Modal pada Perusahaan Perbankan Pemerintah di BEI Periode 2020-2024 - Titi Aslah; Nur Aminah; Henry Waidan; Saprudin; Sofyan Hadi (Media Ilmiah Akuntansi, 2025)
This research aims to analyze the effect of profitability and liquidity levels on the capital structure of state-owned banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The profitability variable is measured using Return on Assets (ROA), while liquidity is measured by the Loan to Deposit Ratio (LDR). In analyzing the data, the researcher uses a quantitative method. The sample in this study consists of state-owned banking companies listed on the Indonesia Stock Exchange for 2020-2024. The variables in this study consist of three ratios: profitability, liquidity, and capital structure. The results of the analysis show that the profitability ratio indicates the inability of most companies to utilize equity in generating profits. Meanwhile, the liquidity ratio indicates that the analysis of the LDR ratio in banking is still within the tolerance limit for banks to be considered healthy.